2000
DOI: 10.1007/s002109900191
|View full text |Cite
|
Sign up to set email alerts
|

PLA2 phosphorylation and cyclooxygenase-2 induction, through p38 MAP kinase pathway, is involved in the IL-1β-induced bradykinin B2 receptor gene transcription

Abstract: We hypothesized that inflammatory mediators such as interleukin-1beta (IL-1beta) might be responsible for the hyperreactivity to bradykinin observed in asthmatic patients. We reported previously that IL-1beta induced a prostanoid-dependent increase in the density of bradykinin B2 receptors in cultured human bronchial smooth muscle cells. Our experiments demonstrate that the rapid prostaglandin E2 (PGE2) synthesis induced by IL-1beta is abolished by cycloheximide, suggesting the involvement of protein synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Recently, it has been shown in neutrophils stimulated with granulocyte/macrophage colony-stimulating factor (GM-CSF) that multiple signaling pathways act in parallel to phosphorylate cPLA 2 , in which both ERK kinases and p38 MAP kinases are involved (Geijsen et al, 2000). In human bronchial smooth muscle cells, interleukin-1b-induced PGE 2 formation is preceded by phosphorylation of cPLA 2 and expression of cyclooxygenase-2 (COX-2), and inhibition of p38 MAP kinase blocked cPLA 2 phosphorylation, COX-2 expression, and PGE 2 synthesis (Schmidlin et al, 2000). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown in neutrophils stimulated with granulocyte/macrophage colony-stimulating factor (GM-CSF) that multiple signaling pathways act in parallel to phosphorylate cPLA 2 , in which both ERK kinases and p38 MAP kinases are involved (Geijsen et al, 2000). In human bronchial smooth muscle cells, interleukin-1b-induced PGE 2 formation is preceded by phosphorylation of cPLA 2 and expression of cyclooxygenase-2 (COX-2), and inhibition of p38 MAP kinase blocked cPLA 2 phosphorylation, COX-2 expression, and PGE 2 synthesis (Schmidlin et al, 2000). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased kinin formation has been demonstrated in pulmonary exudates during allergic reactions in humans (Proud et al, 1983;Naclerio et al, 1988). In addition, BK administration to airways has been shown to induce bronchoconstriction in asthmatics, but not normals (Fuller et al, 1987;Polosa and Holgate, 1990), perhaps due to enhanced B 2 receptor expression 66 in this sensitized patient population (Schmidlin et al, 2000). BK challenge also produces sore throat and rhinitis , and these symptoms are blocked by the potent and selective B 2 receptor antagonist icatibant (Proud et al, 1995).…”
Section: Airway Functionmentioning
confidence: 99%
“…Also, both clinical [45,47] and experimental (animal) studies of depression have shown an increase in tissue concentration of PGE 2 [44]. IL-6, which is also associated with depression, seems to play a crucial role in synthesizing this prostaglandin [48,49], and PGE 2 is itself a potent stimulant for IL-6 production, potentially representing an inflammatory pathogenic loop that may be operating in depressed individuals. It has been shown that tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) attenuate the PGE 2 -synthesis, probably via inhibition of pro-inflammatory cytokines.…”
Section: Systemic Th1-dominated Cytokine Re-sponse In Depressed Indivmentioning
confidence: 99%